On the mixed mode I/II delamination R-curve of E-glass/epoxy laminated composites. (1st July 2017) - Shokrieh, M.M.; Zeinedini, A.; Ghoreishi, S.M.
Abstract: The main effort of the current study is to propose a procedure for prediction of delamination resistance curve (R-curve) of laminated composites under mixed mode I/II loading conditions based on the experimental observations. Hence, two material systems, i.e., E-glass/epoxy and E-glass/MWCNTs-toughened epoxy were tested at a wide range of mixed mode I/II delamination to present R-curves. Each R-curve was characterized by fiber-bridging zone (FBZ) length, critical strain energy release rate at delamination initiation (GTC ) and stable propagation (GTR ) states. It was manifested the magnitude of the FBZ length is constant at different mixed mode I/II loading states for a specific laminate system. Then, using the Benzeggagh and Kenane (B-K) criterion, two relations for computing the GTC and GTR were derived. Finally, according to these findings a relation was obtained to predict the delamination behavior of laminated composites (from delamination initiation to propagation states) under arbitrary mixed mode I/II loading condition.